Tafsir dalam Jejaring Intelektual Indonesia-Hijaz: Kajian Genealogi Al-Ibrīz li Maʿrifati Tafsīr Al-Qur’ān Al-‘Azīz karya Bisri Mustofa - Ahmad Avif Okjilshipia (Nun: Jurnal Studi Alquran dan Tafsir di Nusantara, 2023)
One of the crucial factors to take into account when examining the variety of Qur'anic interpretations is networks of scholarly transmission. In the realm of Indonesian exegesis, the prevalent network originates from Egypt, evident in the significant impact of al-Manār and its subsequent works on the creation of tafsir and Qur'ānic translations in Indonesia. Prior to Egypt's emergence as a popular choice for Indonesian Islamic education, the primary destination was Hijāz. Concerning tafsir, how does this Hijāz route work? This paper explores the interpretation of the Indonesian-Hijaz axis by analysing one of the tafsir works produced by interpreters of the Indonesian-Hijaz route, namely al-Ibrīz li Ma'rifati Tafsīr al-Qur'ān al-'Azīz by Bisri Mustofa. The inquiry at hand pertains to the intellectual network that influences Bisri Mustofa's tafsir work and the manner in which the Indonesian-Hijaz line of interpretation is manifested in al-Ibrīz. This article employs a historiographical approach, utilising a descriptive analytical method. The study concludes that Muhammad ʿAlawī al-Malikī's al-Qawā'id al-Asāsiyyah fi ʿUlum al-Qur'ān is a significant work in the field of ʿulum al-Qur'ān scholarship within the Indonesian-Hijaz axis, and al-Ibrīz is aligned with this book. Likewise, al-Ibrīz exhibits a closer affinity with the works of al-Bayḍāwī, Jalāl al-Dīn Al-Suyūṭī, and ʿAbd al-Raʾuf al-Sinkilī, who had already gained significant readership in Indonesia prior to the impact of al-Manār. This article demonstrates that the various channels through which scholars transmit their interpretations have an impact on the content of their tafsir.